Respiratory syncytial virus mRNA coding assignments. - Huang, Y T (1983)
The polypeptide coding assignments for six of the respiratory syncytial virus-specific mRNAs were determined by translation of the individual mRNAs in vitro. The coding assignments of the RNAs are as follows. RNA band 1 is complex and can be separated into at least two components on the basis of electrophoretic mobility (molecular weights [MWs] approximately equal to 0.21 X 10(6) and 0.31 X 10(6), respectively) that code for three polypeptides of 9.5, 11, and 14 kilodaltons (K). RNA 2 (MW, 0.39 X 10(6)) codes for a 34K polypeptide; RNA 3 (MW, 0.40 X 10(6)) codes for a 26K polypeptide; RNA 4 (MW, 0.47 X 10(6)) codes for a 42K polypeptide; and RNA 5 (MW, 0.74 X 10(6)) codes for a 59K polypeptide. By limited-digest peptide mapping, the 34, 26, and 42K polypeptides synthesized in vitro appeared to be unique. Additionally, peptide mapping showed that the 34, 26, and 42K polypeptides synthesized in vitro were indistinguishable from their counterparts synthesized in infected cells. Thus, the 34, 26, and 42K polypeptides coded for by mRNAs 2, 3, and 4, respectively, were identified as the respiratory syncytial virus phosphoprotein (34K), matrix protein (26K), and nucleocapsid protein (42K), respectively. RNA 5 was shown to code for a 59K polypeptide. The 59K polypeptide synthesized in vitro did not comigrate with any polypeptide specific to infected cells, suggesting that it is a candidate for co- or post-translational modification.